Mutations of CLCN5 in Japanese children with idiopathic low molecular weight proteinuria, hypercalciuria and nephrocalcinosis. - Akuta, N; Lloyd, SE; Igarashi, T; Shiraga, H; Matsuyama, T; Yokoro, S; Cox, J; Thakker, R (1997)
The annual urinary screening of Japanese children above three years of age has identified a progressive renal tubular disorder characterized by low molecular weight proteinuria, hypercalciuria and nephrocalcinosis. The disorder has been observed in over 60 patients and has a familial predisposition. Mutations of a renal chloride channel gene, CLCN5, have been reported in four such families, and we have undertaken studies in additional patients from 10 unrelated, non-consanguineous Japanese families to further characterize such CLCN5 mutations and to ascertain their prevalence. CLCN5 abnormalities we identified in 7 of the 10 unrelated patients and consisted of 5 mutations (2 nonsense, 1 frameshift and 2 missense), 1 deletion and 1 silent polymorphism. A clustering of these mutations in CLCN5 exons 8 and 10 was observed. Over 80% of the CLCN5 mutations could be readily detected by single stranded conformational polymorphism (SSCP) analysis, thereby providing a useful mutation screening method. Our results, which indicate that over 70% of Japanese patients with this renal tubulopathy have CLCN5 mutations, will help in the genetic and clinical evaluation of children at risk from this disorder.